Existence Results for a Class of p-Laplacian Fractional Differential Equations with Integral Boundary Conditions - SunAe Pak; KumSong Jong; KyuNam O; HuiChol Choi (Abstract and Applied Analysis)
In this paper, we investigate the existence and uniqueness of solutions for a class of integral boundary value problems of nonlinear fractional differential equations with p-Laplacian operator. We obtain some existence and uniqueness results concerned with our problem by using Schaefer’s fixed-point theorem and Banach contraction mapping principle. Finally, we present some examples to illustrate our main results.